ESTIMATION OF SELECTION ACCURACY AND RESPONSES OF THE PRODUCTION CHARACTERISTICS USING DIFFERENT SELECTION INTENSITY IN MAGELANG DUCK - Purwantini, D.; Ismoyowati, I.; Santoso, S. A. (Diponegoro University, 2016)
This research was aimed to estimate selection response and accuracy of hatching weight, growth and egg production using different selection intensities in Magelang duck. A nested design was used in this study with experimental material was Magelang duck consisted of 8 male (treatments), 40 female (sub-treatments) and 360 offspring (replicates) and the observed parameter was productive characteristics. Nine DOD from each female were measured for hatching weight and growth up to 8 weeks old. The measured Hen Day Production (HDP) at initial laying for within days. Result showed that different selection intensities (25, 50 and 75%) led to response in 2.968; 1.870 and 0.982 g hatching weight; respectively; 0.00221, 0.00139 and 0.00073 g growth, respectively; and 1.728, 1.088 and 0.571% egg production, respectively. Selection accuracy for hatching weight, growth and egg production was 0.70, 0.76 and 0.51, respectively. Conclusively, the less preserved female proportion, the higher selection intensity value thus the higher selection response. Selection accuracy of production characteristics was based on its heritability value.